Desain Pendidikan Multikultural dalam Pendidikan Islam - Abdul Aziz (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2017)
Indonesian are very rich in ethnic, culture, religion, race, and also language. Indonesian’s diversity at one side could potentially be a nation's progress factor and on the other side could be a serious threat to the emergence of various social problems. In fact, Indonesia currently facing the problem of intolerance and radicalism. It shows that awareness about the importance of respecting diversity and living in diversity is not yet optimal in society. Education, especially religious education occupies strategic role in effort to raise awareness about the importance of coexistence in diversity. This article will review the design of islamic education in multiculturalism perspective.